Bioactive Titanium Oxide Coatings Fabricated on NiTi SMA via Thermal Treatment for Medical Applications. (2016) - Yu, Yonghao; Sun, Tao; Wang, Yue
Abstract: To enhance the biocompatibility, bioactivity and mechanical properties of NiTi shape memeory alloy (SMA), titanium oxide coatings were fabricated via thermal treatments at 400 and 600 °C, respectively. The surface morphology, elemental distribution and phase composition of the untreated and thermal treated samples were characterized using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD), respectively. The comparative study was carried out for the thermal treated samples at different temperatures in terms of surface Ni content and bioactivity, then the optimal temperature of the thermal treatment was obtained.